Geographic location and year determine virulence, and year determines genetic change, in populations of Neopseudocercosporella capsellae. (7th October 2019) - Murtza, T.; You, M. P.; Barbetti, M. J.
Abstract : White leaf spot ( Neopseudocercosporella capsellae ) can be severe and problematic worldwide across both horticultural and oilseed Brassicaceae, including susceptible rapeseed. In this study, 82 isolates from 2015 and 106 isolates from across Australia in 2016 were first assessed for their virulence against three different rapeseed ( Brassica napus ) cultivars. For both years there were significant ( P  < 0.001) differences. Also, there were significant (all P  < 0.001) differences between isolates in each year, and between cultivars. For 2016 isolates, there were also significant differences ( P  < 0.001) between isolates across three different Australian states, and a significant interaction ( P  < 0.001) between isolates with cultivars. Of the three Australian states, isolates from Victoria were most virulent. Among tested cultivars, cv. Scoop was most susceptible. Subsequently, phylogenetic analysis of 114 of these same 2015 and 2016 isolates showed current isolates clustered separately from the majority of 2005 N. capsellae isolates collected from Western Australia a decade earlier, confirming significant genetic change within N. capsellae populations over the past decade. However, isolate clusters showed no association with geographical location. The results suggest that phylogenetic association among 2005 and 2015–2016 N. capsellae isolates is complementary with pathogenicity variations explained by geographically different N. capsellae pathogen populations. Neopseudocercosporella capsellae populations are evolving rapidly, challenging management through host resistance at a time of increasing incidence and severity of white leaf spot disease over the past decade. The outcome is well illustrated by cv. Scoop, previously resistant to 2005 isolates but moderately susceptible to 2015 and highly susceptible to 2016 isolates.